PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUAL) BERBANTU GEOBOARD TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Mega Purnama Sari, Nur; Fendrik, Muhammad; Hainul Putra, Zetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical conceptual understanding is a student's ability to grasp the meaning of a mathematical concept, explain it further, relate it to other concepts, and apply it in various situations. Elementary school students' low mathematical conceptual understanding is a significant problem in mathematics learning. This study aims to determine the effect of the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model, assisted by a geoboard, on elementary school students' mathematical conceptual understanding. This study used a quantitative approach with a quasi-experimental method involving two groups: the experimental group (N = 27) who received instruction using the SAVI model assisted by a geoboard, and the control group (N = 24) who followed conventional teaching methods. The non-equivalent control group design used a cluster sampling technique, with a multiple-choice test as the instrument. The results showed that the average pretest score for the experimental class was 52.59 and the control class 53.75. After the treatment, the average posttest score for the experimental class increased to 84.44, while the control class's score was 61.88. The results of the Independent Sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect. Thus, the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model assisted by geoboards has a positive effect on improving elementary school students' understanding of mathematical concepts.